Overcoming MCL-1-driven adaptive resistance to targeted therapies - Kris C. Wood (Nature Portfolio, 2020)
Two complementary studies in Nature Communications define a critical role for the anti-apoptotic protein MCL-1 as a driver of adaptive survival in tumor cells treated with oncogene targeted therapies, providing a rationale for combining these agents with newly developed MCL-1 inhibitors in the clinic.